2020
DOI: 10.1063/5.0031484
|View full text |Cite
|
Sign up to set email alerts
|

MOCVD growth of high purity Ga2O3 epitaxial films using trimethylgallium precursor

Abstract: We report on the growth of β-Ga2O3 thin films using trimethylgallium (TMGa) as a source for gallium and pure O2 for oxidation. The growth rate of the films was found to linearly increase with the increase in the molar flow rate of TMGa and reach as high as ∼6 μm/h at a flow rate of 580 μmol/min. High purity, lightly Si-doped homoepitaxial β-Ga2O3 films with a good surface morphology, a record low temperature electron mobility exceeding 23 000 cm2/V s at 32 K, and an acceptor concentration of 2 × 1013 cm−3 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(58 citation statements)
references
References 45 publications
0
53
0
Order By: Relevance
“…By using N 2 O as an oxygen precursor, the background doping in the films can be reduced to ∼10 14 cm –3 . By reducing the acceptor densities to 2 × 10 13 cm –3 , a record high low temperature hall mobility of 23,000 cm 2 /V s has been achieved . The combination of high-room temperature and low-temperature mobilities confirms the high quality of MOVPE-grown β-Ga 2 O 3 thin films.…”
Section: Introductionmentioning
confidence: 58%
“…By using N 2 O as an oxygen precursor, the background doping in the films can be reduced to ∼10 14 cm –3 . By reducing the acceptor densities to 2 × 10 13 cm –3 , a record high low temperature hall mobility of 23,000 cm 2 /V s has been achieved . The combination of high-room temperature and low-temperature mobilities confirms the high quality of MOVPE-grown β-Ga 2 O 3 thin films.…”
Section: Introductionmentioning
confidence: 58%
“…C O -H, finally, was found to act as an acceptor over the entire range of alloy compositions, behaving very similarly to a N O substitutional impurity and explaining experimental observations of carbon-related compensation in Ga 2 O 3 grown by MOCVD. [33,34] Our findings indicate that the presence of hydrogen or carbon may interfere with controlled low-level Si doping in (Al x Ga 1−x ) 2 O 3 alloys, and our detailed results can be used to devise growth or processing conditions to avoid this.…”
Section: Discussionmentioning
confidence: 93%
“…We propose that the C O -H complexes may have a distinct impact on MOCVD-grown Ga 2 O 3 . Seryogin et al [33] grew Ga 2 O 3 using a trimethylgallium (TMGa) precursor, which is known to potentially lead to increased C incorporation. They found that films grown with a lower O 2 /TMGa ratio were significantly more resistive and also contained significantly more carbon.…”
Section: Co-h Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…MOCVD is capable of controlling the doping densities up to ~10 19 cm -3 with low dislo-Dinusha Herath Mudiyanselage, Dawei Wang, and Houqiang Fu are with Department of Electrical and Computer Engineering, Iowa State University, Ames, IA 50011 USA (e-mail: houqiang@iastate.edu). cation densities, providing high-quality epitaxial layers [10,11]. Recently, β-Ga2O3 power devices have been demonstrated with encouraging performance such as high breakdown voltages, high critical electric fields, high currents, and excellent thermal stability [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%